2021
DOI: 10.3389/fpsyg.2021.747330
|View full text |Cite
|
Sign up to set email alerts
|

Leader Narcissism and Employee Organizational Citizenship Behavior Directed Toward the Leader: Roles of Perceived Insider Status and Need for Self-Esteem

Abstract: Based on self-concept theory, the present study proposed and empirically tested the impact of leader narcissism on employee organizational citizenship behavior directed toward the leader (OCB-L), highlighting the mediating role of perceived insider status and the moderating role of need for self-esteem in this relationship. Based on an analysis of 161 two-stage matched leader-employee dyads, the hypotheses were tested and the results showed that the leader narcissism had a negative direct effect on employee OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…Another study found a negative association between leader narcissism and OCB. The link was mediated by perceived insider status ( Wang et al, 2021 ). These studies confirm the nomological net of perceived insider status in managerial and leadership behaviors.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Another study found a negative association between leader narcissism and OCB. The link was mediated by perceived insider status ( Wang et al, 2021 ). These studies confirm the nomological net of perceived insider status in managerial and leadership behaviors.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Perceived insider status (PIS) depicts employees’ self-categorizations of the psychological relationship between themselves and their organizations ( Stamper and Masterson, 2002 ; Chen and Aryee, 2007 ; Dai and Chen, 2015 ). A high level of PIS can generate various benefits ( Boswell et al, 2012 ) such as a stronger sense of belonging ( Schaubroeck et al, 2017 ), higher organizational commitment ( Wang et al, 2021 ), higher satisfaction and retention ( Armstrong-Stassen and Schlosser, 2011 ; Knapp et al, 2014 ; Chen et al, 2017 ), higher well-being in the workplace ( Findler et al, 2007 ), less follower territorial behavior ( Liu et al, 2021 ), and more organizational citizenship behaviors ( Caron et al, 2019 ). Noteworthy is that we chose PIS rather than organizational identification because scholars have found PIS is particularly salient in the Chinese context ( Hui et al, 2015 ) due to the highly collective and power distance-orientated culture.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…During their tenure, head teachers can be trained on conflict management, emotional manipulation and effective leadership behaviors, to restrain their stress resulting from different types of responsibilities, avoid words or gestures that may be misinterpreted and send clear messages to their staff. Supervisor education through seminars, training programs and workshops is considered vital (Wang et al, 2021). Furthermore, school managers can reduce the negative association between incivility and negative employees' attitudes (e.g.…”
Section: Contribution and Implicationsmentioning
confidence: 99%